Complications Following Operatively Treated Ankle Fractures in Insulin- and Non–Insulin-Dependent Diabetic Patients. Issue 3 (June 2018) - Haddix, Kevin P.; Clement, R. Carter; Tennant, Joshua N.; Ostrum, Robert F.
Background : Diabetics with ankle fractures experience more complications than the general population, but it is unclear whether complications differ between type 1 and 2 diabetics and between insulin- and non–insulin-dependent diabetics. This study aims to determine if there is a difference in postoperative complication rates between these groups. Methods : An administrative health care database from a large commercial insurer was queried to identify operatively treated ankle fractures in patients with type 1 (T1D), type 2 (T2D), type 2 insulin-dependent (T2ID), and type 2 non–insulin-dependent (T2NID) diabetes. Postoperative complications were identified to include postoperative stiffness, posttraumatic arthritis, amputation, implant removal, and infection. Subgroup analysis was performed to control for comorbidities. Results : A total of 20 703 closed and 2873 open operatively treated ankle fractures were identified. Patients with T1D experienced higher rates of amputation, postoperative infection, and total complications than patients with T2D (P < .05). Patients with T2ID experienced higher rates of amputation, infection, and total complications than those with T2NID (P < .0001). Subgroup analysis controlling for comorbidities showed a higher total complication rate for T1D compared with T2D in closed ankle fractures (P < .02) and for T2ID compared with T2NID in both open and closed ankle fractures (P < .0001). Conclusions : Patients with T1D and T2ID have higher complication rates than patients with T2D and T2NID, respectively. Foot and ankle surgeons should be cautioned not to classify diabetics as one cohort and should use these findings to stratify risk among this patient population. Levels of Evidence : Level III: Diagnostic